Performance analysis in high-level volleyball: The challenge of defining the set score - Klaricic, I.; Cvenic, J.; Ajman, H. (10th International scientific conference on kinesiology. Book of abstracts, 2024)
In performance analysis in volleyball the set score is defined in various manners, e.g. victory / defeat, a point difference etc. The purpose of this study was to introduce the relative point difference as a more appropriate variation of defining the set score in volleyball. For this purpose, 40 volleyball sets were randomly selected (Men`s European Volleyball League, 2011 and 2012). The predictor variables were efficiency coefficients of the serve, reception, spike, block and dig. A criterion variable was the set score. The set score was defined in four different ways, relative point difference, the point difference, the category according to the range of point difference, and victory / defeat. Four multiple linear regression analyses were conducted to determine the relationship between the efficiency coefficients of the volleyball game phases and the set score, one for each manner of defining the set score. The results showed that victory / defeat was the variation with the lowest amount of explained variance of the set score, only 47.5%. Next was the category with 69.0%, then the point difference with 70.7%. The relative point difference was the variation of the set score that had the highest amount of common variance with the efficiency of the game phases, 75.2%. Relative point difference differentiates the sets with the two point difference but different total numbers of rallies played in a set. The set score that is not adequately defined could enable the determination of the existing phenomenon.